1997
DOI: 10.1063/1.365593
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions between nickel thin films and GaN

Abstract: Thin Ni films on GaN were annealed at temperatures between 400 and 900°C in N 2 , Ar, and forming gas and were analyzed using glancing angle x-ray diffraction and Auger depth profiling. The first indication of an interfacial reaction was found after an anneal at 600°C for 1 h, after which Ga was observed to be dissolved in the face-centered cubic Ni film. The extent of dissolution increased with continued annealing. After annealing at 750°C for 1 hr in either N 2 or Ar, greater intermixing occurred. The reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 8 publications
(9 reference statements)
9
45
0
1
Order By: Relevance
“…The nitrogen vacancy in turn compensates the acceptor dopants at the metal/p-GaN interface. Several groups have already reported similar findings on these issues [7,8,9]. In addition, the presence of the high resistive Ni 3 N and Ni 4 N phases at the metal-semiconductor interface at the annealing temperature greater than 500 o C can also result in higher contact resistance [10].…”
Section: Resultssupporting
confidence: 64%
“…The nitrogen vacancy in turn compensates the acceptor dopants at the metal/p-GaN interface. Several groups have already reported similar findings on these issues [7,8,9]. In addition, the presence of the high resistive Ni 3 N and Ni 4 N phases at the metal-semiconductor interface at the annealing temperature greater than 500 o C can also result in higher contact resistance [10].…”
Section: Resultssupporting
confidence: 64%
“…A significant dissolution of Ga in Ni was also observed as the first step in the reaction of a Ni film with GaN. 18,27 The similarity between Ni and Pt is mentioned further in the following section.…”
Section: Resultsmentioning
confidence: 99%
“…13 large N 2 pressure burst at 600°C in ultrahigh vacuum. 27 Venugopolan et al observed the release of N 2 gas from the ͗GaN͘/Ni reaction at 750°C in either Ar or N 2 , even when the nitrogen pressure was 1 atm, 18 as opposed to 600°C in vacuum. 27 In the present study, the loss of nitrogen is indicated by blister formation already at 550°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the interfacial reactions between metal and GaN have been carried out in the viewpoint of thermal stability [7][8][9]. However, the results are still conflicting, and moreover, important issues such as the nature of the interfacial reactions and microstructures of metal/p-GaN are remaining unclear.…”
Section: Introductionmentioning
confidence: 99%